Post - War Education, 1943 (United Kingdom, 1943)
1943 1939-1945 "Post - War Education, 1943" [HFR0096], 1943 This pamphlet by J.P.M. Millar, General Secretary of the National Council of Labour Colleges, outlines the NCLC proposals for the restructuring of educational policy after the war and includes a memo submitted to the TUC Education Committee. The cartoon on the front cover is by J.F. Horrabin.